Development of the international orbital Cavernous Hemangioma Exclusively Endonasal Resection (CHEER) staging system. Issue 7 (27th February 2019) - El Rassi, Edward; Adappa, Nithin D.; Battaglia, Paolo; Castelnuovo, Paolo; Dallan, Iacopo; Freitag, Suzanne K.; Gardner, Paul A.; Lenzi, Ricardo; Lubbe, Darlene; Metson, Ralph; Moe, Kris S.; Muscatello, Luca; et al.
Abstract : Background: Orbital cavernous hemangiomas (OCH) are the most common adult orbital tumor and represent an ideal index lesion for endonasal orbital tumor surgery. In order to standardize outcomes reporting, an anatomic‐based staging system was developed. Methods: An international, multidisciplinary panel of 23 experts in orbital tumor surgery was formed. A modified Delphi method was used to develop the cavernous hemangioma exclusively endonasal resection (CHEER) staging system with a total of 2 rounds being completed. Results: Tumors medial to a plane along the long axis of the optic nerve may be considered amenable for an exclusively endonasal resection. In select cases, tumors may extend inferolaterally if the tumor remains below a plane from the contralateral naris through the long axis of the optic nerve (ie, plane of resectability [POR]). This definition reached consensus with 91.3% of panelists in agreement. Five stages were designed based on increasing technical resection difficulty and potential for morbidity. Stages were based on the relationship of the tumor to the extraocular muscles, the inferomedial muscular trunk of the ophthalmic artery (IMT), and orbital foramina. Staging by anatomic location also reached consensus with 87.0% of panelists in agreement. Size was not included in the staging system due to the lack of agreement on the contribution of size to resection difficulty. Conclusion: Endoscopic orbital tumor surgery is a nascent field with a growing, yet heterogeneous, body of literature. The CHEER staging system is designed to facilitate international, high‐quality, standardized studies establishing the safety, efficacy, and outcomes of endonasal resection of OCH.